Study of the Effects of Flame Perturbation by High-Speed Schlieren Imaging - Ahmad Zamani Masnizam Bin Abdullah Zawawi, Ahmad Zamani Masnizam (Universiti Teknologi Petronas, 2008)
The importance of flame triggers study on flame’s characteristics. One of the most important characteristics of flame is the flame front, as it determines the interface between the unburned reactant and the burned product. The boundary of a flame usually cannot be seen clearly by naked eyes.